A Tribute to Peter H Seeburg (1944–2016): A Founding Father of Molecular Neurobiology - Wisden, William (Frontiers in Molecular Neuroscience, 2016)
On 22nd August 2016, the fields of molecular neurobiology and endocrinology lost one of their pioneers and true giants, Peter Seeburg, who died aged 72, a day after his birthday. His funeral ceremony took place in Heidelberg where he had worked since 1988, first as a professor at the University of Heidelberg (ZMBH) and then since 1996 as a director of the Max Plank Institute (Dept. of Molecular Neurobiology). Many of Peter’s former colleagues, students and postdocs came together with his family members to celebrate his life. Touching eulogies were given by no less than two Nobel prize winners: the physiologist Bert Sakmann, who collaborated with Peter for many years, and the developmental biologist Christiane Nüsslein-Vollhard, who was a friend and fellow PhD student with Peter. His professional contemporary, Heinrich Betz, gave a warm and endearing assessment of Peter’s contributions to the field of molecular neurobiology. One of Peter’s sons, Daniel P. Seeburg, now a neuroradiologist in the USA, and biotechnologist Karoly Nikolics, one of Peter’s friends from the days of Genentech, both emotionally summed up the warm and intense character of the man that many of his former students and postdocs knew.